Respostas
respondido por:
2
a)- (a+x)·(a-1)
= a²- a +xa -x
= a(a-1+x) - x
________________________________________________________
b)- (a-x)·(a+1)
= a² + a - xa -x
= a(a+1-x) -x
__________________________________________________________
c)- (a-x)·(a-1)
= a² - a -xa +x
= a(a-1-x) +x
__________________________________________________________
d)- (a+x)·(a+1)
= a² + a +xa + x
a(a+1+x) +x
Boa sorte!
respondido por:
0
Resposta:
.
...................................... ............
......
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás